Co-recognition of β-glucan and chitin and programming of adaptive immunity to Aspergillus fumigatus - Amarsaikhan, Nansalmaa; Templeton, Steven P. (Frontiers in Microbiology, 2015)
The prevalence of fungal infections has increased concurrently with increases in immune suppressive therapies and susceptible individuals. Opportunistic fungal pathogens such as Aspergillus fumigatus may exhibit invasive growth and dissemination resulting in a high mortality rate. Herein, we discuss how immune sensing of germination directs innate immune responses and programs adaptive responses that could promote or impair immune protection during periods of heightened susceptibility. In infected individuals, Th1 responses are the most protective, while Th2 responses lead to poor disease outcomes. In particular, the roles of β-glucan and chitin co-recognition in shaping Th1- and Th2-type immunity to fungal infection are explored. We discuss how fungal responses to environmental stresses could result in decreased immune protection from infection, particularly in response to anti-fungal drugs that target β-glucan synthesis. Furthermore, we consider how experimental modulation of host-pathogen interactions might elucidate the mechanisms of protective and detrimental immunity and the potential of current and future studies to promote the development of improved treatments for patients that respond poorly to existing therapies.